2023
DOI: 10.3390/ijms24087290
|View full text |Cite
|
Sign up to set email alerts
|

Integration of mRNA and miRNA Analysis Reveals the Post-Transcriptional Regulation of Salt Stress Response in Hemerocallis fulva

Abstract: MicroRNAs (miRNAs) belong to non-coding small RNAs which have been shown to take a regulatory function at the posttranscriptional level in plant growth development and response to abiotic stress. Hemerocallis fulva is an herbaceous perennial plant with fleshy roots, wide distribution, and strong adaptability. However, salt stress is one of the most serious abiotic stresses to limit the growth and production of Hemerocallis fulva. To identify the miRNAs and their targets involved in the salt stress resistance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Subsequently, alfalfa seedlings were treated with salt, drought, cold, and heat stress, and qRT-PCR experimentally verified their expression patterns. As reported by Zhou et al [ 55 ], ARF12 might play central roles in the regulation of NaCl-responsive genes. In addition, AcARF5 can positively regulate salt stress and drought stress in kiwifruit ( Actinidia chinensis ) [ 56 ].…”
Section: Discussionmentioning
confidence: 75%
“…Subsequently, alfalfa seedlings were treated with salt, drought, cold, and heat stress, and qRT-PCR experimentally verified their expression patterns. As reported by Zhou et al [ 55 ], ARF12 might play central roles in the regulation of NaCl-responsive genes. In addition, AcARF5 can positively regulate salt stress and drought stress in kiwifruit ( Actinidia chinensis ) [ 56 ].…”
Section: Discussionmentioning
confidence: 75%
“…The adverse effects of salt alkali stress on Xanthium sibiricum Patr. are reduced via exogenous BR (Zhou et al, 2023). Similar research revealed that exogenous BR sprayed on cucumber leaves during salt alkali stress reduced the concentrations of ROS, MDA, and electrical conductivity in plant leaves while dramatically enhancing the activity of many antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 70%
“…Salt stress is a serious abiotic stresses limiting H. fulva growth and production. In the study of Zhou et al [11], miRNA expression was significantly different in the roots and leaves of H. fulva. miRNAs are non-coding small RNAs that play a post-transcriptional regulatory role in plant growth development and response to abiotic stress.…”
Section: Salt Stressmentioning
confidence: 94%